Clinical and economic consequences of medication nonadherence: a review of systematic reviews - Achterbosch, Maria; Aksoy, Nilay; Obeng, George D.; Ameyaw, David; Ágh, Tamás; van Boven, Job F. M. (Frontiers in Pharmacology, 2025)
BackgroundMedication efficacy observed in clinical trials may differ from its effectiveness during real-world usage. Medication nonadherence is one of the key factors being responsible for this efficacy-effectiveness gap. The World Health Organization estimated that only 50% of chronic medication users is adherent and nonadherence results in both negative health outcomes for the patient and higher societal costs. An overview of the consequences across disease groups may allow some comparison and could contribute to identification of priority clinical areas.ObjectiveWe aimed to provide an overview the impact of nonadherence on clinical and economic outcomes.MethodWe narratively reviewed systematic reviews published between 2014 and 2024 on the effect of medication nonadherence on clinical and economic outcomes.ResultsOverall, 43 systematic reviews were identified, including over 410 original studies on clinical outcomes and 174 on economic outcomes, covering different clinical areas (e.g., organ transplantation, cardiovascular diseases, diabetes, depression and chronic lung diseases [asthma/COPD]). Beyond diminished treatment effects, medication nonadherence has been associated with elevated mortality, increased healthcare utilization (including hospital admissions), and higher direct (e.g., more healthcare provider visits) and indirect financial cost burden (e.g., work productivity losses due to absenteeism and presenteeism) for patients and society.ConclusionMedication nonadherence is associated with poor clinical and economic outcomes across disease areas. Given the significant impact of nonadherence, raising awareness among healthcare professionals and policymakers, early stakeholder engagement in intervention design, and eventually implementation of cost-effective interventions on both health policy, system and individual patient level are urgently required.